Death Valley National Park - Petersen, David 1946- (New York Children's Press, 1996)
Depicts the scenery and wildlife at Death Valley National park and recounts the efforts to save the area from destruction by mining
American Corner
Includes bibliographical references (p. 44) and index
5 8 11
Keywords: National parks and reserves; Death Valley National Park (Calif. and Nev.) -- Juvenile literature